Strategic Human Resource Management in Higher Education: An AMO Framework Analysis of Lahore University of Management Sciences - Raza, Muhammad; Nasrulloh, Ahmad; Meghwar, Qeemat Rai (Jurnal Akuntabilitas Manajemen Pendidikan, 2025)
This study examine the strategic human resource management (HRM) practices at Lahore university of management sciences (LUMS) Pakistan, focusing on their alignment with institutional goals and their impact on faculty development and students success. Using a qualitative research approach, the study explores four key HRM pillars: recruitment, training and development, performance evaluation and organizational culture. LUMS implements a merit-based and inclusive recruitment model, attracting highly qualified faculty to promote academic excellence. Training initiatives like the peer-driven facilitators training programs and learning institute reflect a strong commitment to pedagogical development. Performances management is structures through SAP success factors, facilitating goals alignment, regular appraisal and feedback. LUMS foster a people-centered organizational culture based on diversity, trust, and growth. Grounded in the Ability-Motivation-Opportunity (AMO) theory and strategic HRM framework, the findings underscore how LUMS's integrated HRM model enhances academic staff performance and plays a vital role in promoting educational innovation, quality and improved students outcomes.